Pedagogical Innovation in Islamic Education: (A Systematic Literature Review of Strategies to Improve Student Engagement and 21st Century Skills) - Atin Priatin Munawaroh; Aoulia Aoulia; Mohammad Alwi (Lembaga Publikasi Ilmiah Universitas Islam Bunga Bangsa Cirebon, 2026)
Strategies and instructional methods constitute an inseparable unity. As professional educators, teachers are required to master various learning strategies and methods. In addition, innovations in instructional strategies and methods continue to be developed by teachers in order to respond to contemporary challenges, particularly within the context of independent learning (Merdeka Belajar). The purpose of this study is to identify and explore innovations in learning. This study is based on the assumption that teacher-centered approaches possess many weaknesses, whereas in student-centered approaches, the role of the teacher is to assist students in discovering facts, concepts, or principles independently. Therefore, to support learning efforts aimed at shaping students’ creative, interactive, and innovative character in classroom learning processes, innovation in learning is necessary in order to align education with current technological developments.